2013 IEEE Sixth International Conference on Software Testing, Verification and Validation 2013
DOI: 10.1109/icst.2013.20
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of the Statement Deletion Mutation Operator

Abstract: Abstract-Mutation analysis is widely considered to be an exceptionally effective criterion for designing tests. It is also widely considered to be expensive in terms of the number of test requirements and in the amount of execution needed to create a good test suite. This paper posits that simply deleting statements, implemented with the statement deletion (SDL) mutation operators in Mothra, is enough to get very good tests. A version of the SDL operator for Java was designed and implemented inside the muJava … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 29 publications
5
51
0
Order By: Relevance
“…SDL-mutation [15] is a one-op mutation version that uses Statement Deletion (SDL). Results showed that SDLmutation yields huge savings in the cost of mutation testing without a significant loss of effectiveness [14].…”
Section: Deletion Mutation Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…SDL-mutation [15] is a one-op mutation version that uses Statement Deletion (SDL). Results showed that SDLmutation yields huge savings in the cost of mutation testing without a significant loss of effectiveness [14].…”
Section: Deletion Mutation Operatorsmentioning
confidence: 99%
“…The usual way to assess an operator's effectiveness is to first design a test set that kills all of its mutants, and then find how many mutants that test set kills of the complete set of mutants. In previous experiments, SDL achieved 92% effectiveness for Java [14]. Second, the cost of using SDL is low.…”
Section: Deletion Mutation Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…By doing this transformation, OAAN and OBBN apply in those cases.  We included SSDL because recent studies have pointed to the usefulness of this operator [41]. Moreover, the comparable study by Baker and Habli [32] analyses this operator, so it is interesting to observe if mutants from this operator are also effective in detecting deficiencies in our branch-adequate test suites.…”
Section: G Cost Reduction Techniquesmentioning
confidence: 99%
“…These mutants were generated by a single mutation operator, Statement Deletion (SSDL). We chose SSDL for two reasons: (1) it is universally applicable to all programs; and (2) it has been studied in recent papers as an alternative to using the complete set of mutation operators [1,7,8].…”
Section: Methodsmentioning
confidence: 99%